Safety and efficacy of Cinacalcet in children aged under 3 years on maintenance Dialysis - Bernardor, Julie; Flammier, Sacha; Zagozdzon, Ilona; Lalayiannis, Alexander D.; Koster-Kamphuis, Linda; Verrina, Enrico; Dorresteijn, Eiske; Guzzo, Isabella; Haffner, Dieter; Shroff, Rukshana; Schmitt, Claus P.; Bacchetta, Justine (Kidney international. Reports, 2024)
Introduction - Secondary hyperparathyroidism (sHPT) is particularly severe in rapidly growing infants in dialysis. Although cinacalcet is effective and licensed in dialysis in children aged >3 years, its efficacy and safety for children aged <3 years is unknown. - Methods - We identified 26 children aged <3 years who were on dialysis and treated with cinacalcet between 2009 and 2021 in 8 European pediatric centers. - Results - Median (interquartile range) age at the start of cinacalcet was 18 (interquartile range: 11-27) months, serum parathyroid hormone (PTH) was 792 (411-1397) pg/ml, corresponding to 11.6 (5.9-19.8) times the upper limit of normal (ULN). Serum calcium was 2.56 (2.43-2.75) mmol/l, and serum phosphate 1.47 (1.16-1.71) mmol/l. Serum 25-OH vitamin D (25-OHD) was 70 (60-89) nmol/l, 3 children were vitamin D deficient (<50 nmol/l). The initial cinacalcet dose was 0.4 (0.2-0.8) mg/kg/d and the maximum dose was 1.1 (0.6-1.2) mg/kg/d. The median follow-up under cinacalcet was 1.2 (0.7-2.0) years. PTH decreased to 4.3 (2.2-7.8) times the ULN after 6 months, to 2.0 (1.0-5.3) times ULN after 12 months, and to 1.6 (0.5-3.4) times thereafter (P = 0.017/0.003/<0.0001, log-transformed PTH). Seven of the 26 infants developed 10 hypocalcemic episodes <2.10 mmol/l. Oral calcium intake was 84% (66%-117%) of recommended nutrient intake at start, 100% (64%-142%) at 3 months and declined to 78% (65%-102%) at 12 months of therapy. Three children developed clinical signs of precocious puberty. - Conclusion - Cinacalcet efficiently controlled severe sHPT in children aged <3 years and was associated with hypocalcemic episodes (similar to what is observed in older children) and precious puberty, thereby mandating meticulous control of calcium (considering nutrition, supplementation, and dialysate) and endocrine changes.